Fundamentals Of Molecular Spectroscopy [4th ed.] - Banwell, Colin N.; Mccash, Elaine M. (UK: Mcgraw Hill, 2016)
This revision of Dr. Branwell's highly popular text retains the features which have made it so attractive to students and lecturers over the years. It remains an elementary and non-mathematical introduction to molecular spectroscopy that emphasizes the overall unity of the subject and offers a pictorial perception rather than a mathematical description of the principles of spectroscopy.